Pengembangan Objek Wisata ‘’CIMA HILL VIEW’’ di Desa Terong, Kabupaten Bantul - Zuhud Rozaki; Widodo; Muhammad Fauzan (Universitas Lancang Kuning, 2021)
Bantul Regency is contributing the highest tourists number in Special Region of Yogyakarta (DIY). Terong Village has potency to be tourism village in this regency, it can be seen as this area is located in the middle of Yogyakarta City and Dlingo Sub-District, many trourist through Terong Village to visit tourism places in Dlingo Sub-District. Effort to optimize the potency of this villade has been started to built CIMA HILL VIEW. This community service activity aims to empower people around CIMA HILL VIEW to be more aware the potency of their village and support the tourism development. Activities that have been done were increasing the awareness regarding tourism potency, developing facilities in CIMA HILL VIEW, and promote this tourist place trough social media, which is Instagram. It hopes that CIMA HILL VIEW can develop and become the part of people economy.